Framework proposal for ecodesign integration on product portfolio management - Paula Pinheiro, Marco Antonio [UNESP]; Jugend, Daniel [UNESP]; Demattê Filho, Luiz Carlos; Armellini, Fabiano (Elsevier, 2018)
Although many studies on product portfolio management (PPM) and ecodesign exist, there are few investigations that analyze these areas in an integrated way. They are normally conceptually separated, with very few theoretical and empirical interactions evident in the literature. This article proposes a theoretical framework that integrates ecodesign practices, methods, and tools with portfolio management during the product planning stage. For the development of this framework, a systematic analysis and literature review of both PPM and ecodesign were conducted. The framework subsequently developed was evaluated through a pilot test within two companies that develop products derived from Brazilian biodiversity. In terms of results, it presents a set of practices that are associated with the following dimensions: Guides, Methods, and Tools; Organization; and Strategy. After presenting the evaluation of the framework by the companies, practices are proposed which can be useful for the integration of ecodesign into PPM, such as adoption of the Project Management Office (PMO) and the use of social media.
Keywords: Development of environmentally sustainable products; Ecodesign; Green innovation; Green product development; Product portfolio; Sustainable design